The needs of European farmers in the dairy cattle and small ruminant sector - Klein, Renáta; Oláh, János; Morgan-Davies, Claire; Brocard, Valérie; Bácsi, Eszter Ilona; Török, Evelin; Gulyás, Gabriella; Czeglédi, Levente (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
The Horizon 2020 research programm Resilience for Dairy (R4D), which focuses on the social, economic and environmental resilience of the dairy cattle sector, and Sm@ll Ruminant Technologies (Sm@RT), which focuses on the technological potential of PLF (Precision Livestock Farming) for the small ruminant sector, were based on a stakeholder needs assessment. A questionnaire survey was carried out to assess the needs of farmers, consultants, veterinarians and researchers on the topics covered. Regarding dairy farms, 535 responses from 15 countries and 669 responses from 8 countries in the small ruminant sector were collected and processed.There were overlaps between the needs of the cattle and small ruminant sectors examined in similar areas. The main need in both sectors was reduction of human labour demand. Cattle farmers defined this as work-life balance, while small ruminants by facilitating flock/ herd management. In addition to these, there are also demands for animal health, milking and professional communication. 81% of farmers surveyed said that improving the welfare of their cows was the most important issue. This answer was particularly typical (84%) in dairy farms with more than 100 cows. More than half of the responding shepherds ranked weight crate first as the most advantageous technology for them.Both projects were based on a needs assessment to find solutions relevant to the sector, which could ensure the longterm sustainability of the European dairy cattle and small ruminant sectors.